Pandemics, Public Health and Social Science - Ronnie Moore (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
The PREPARE1 research consortium is a European Union (EU) funded five-year (plus) investigation (additional funding and aims were added), set up to assess public health and clinical preparedness in the event of an Infectious Disease (ID) pandemic. The project, initiated in 2014 represents an international, multidisciplinary investigation conducted by a range of research clinicians and social scientists, aiming (as a first phase) to identify key structural, behavioural and cultural barriers to the rapid implementation of large multi-site clinical studies in Europe (Work package 1, see EARL Reports)2,3.